2013
DOI: 10.1088/0031-9155/58/22/7937
|View full text |Cite
|
Sign up to set email alerts
|

Erroneous cardiac ECG-gated PET list-mode trigger events can be retrospectively identified and replaced by an offline reprocessing approach: first results in rodents

Abstract: The assessment of left ventricular function, wall motion and myocardial viability using electrocardiogram (ECG)-gated [(18)F]-FDG positron emission tomography (PET) is widely accepted in human and in preclinical small animal studies. The nonterminal and noninvasive approach permits repeated in vivo evaluations of the same animal, facilitating the assessment of temporal changes in disease or therapy response. Although well established, gated small animal PET studies can contain erroneous gating information, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…A recent work [7] has shown that the ECG-based CGS in small animals is not perfect, and some errors may be expected. In our case, about 5 % of the heartbeats are missed by the ECG.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent work [7] has shown that the ECG-based CGS in small animals is not perfect, and some errors may be expected. In our case, about 5 % of the heartbeats are missed by the ECG.…”
Section: Discussionmentioning
confidence: 99%
“…In some preclinical settings, this additional equipment may not be available, or it may not work properly during an acquisition, and furthermore, it is usually rather cumbersome to use in small animals. Moreover, the use of these systems requires the integration of software, hardware, and user input, which could be problematic [7]. Recently, it has been shown that the CGS derived from an ECG may have a significant amount of errors, such as missing heartbeats, which may worsen the quality of the gated images [7].…”
Section: Ardiac Positron Emission Tomography (Pet) Is a Well-mentioning
confidence: 99%
See 2 more Smart Citations
“…In the work of Todica et al, ECG data were processed off-line to embed the triggers into the list-mode data prior to image reconstruction, recognizing that accurate temporal synchronization between the ECG and the PET scanner is essential. 12 Their implementation is vendor specific due to the unique list-mode file format; utilization of a Figure 1. Simulation of a phantom image (left) and with an image acquisition, reconstruction, and cardiac motion mimicking blur, both without (center) and with (right) the presence of sinusoidal horizontal motion.…”
mentioning
confidence: 99%